Molecular cytogenetic characterization of a critical region in Bands 7q35-q36 commonly deleted in mlignant myeloid disorders - Döhner, Konstanze; Brown, Jill; Hehmann, Ute; Hetzel, Claudia; Stewart, Janet; Lowther, Gordon; Scholl, Claudia; Fröhling, Stefan; Cuneo, Antonio; Tsui, Lap C.; Lichter, Peter; Scherer, Stephen W.; et al. (Blood, 1998)
Loss of chromosome 7 (−7) or deletion of the long arm (7q−) are recurring chromosome abnormalities in myeloid leukemias. The association of −7/7q− with myeloid leukemia suggests that these regions contain novel tumor suppressor gene(s), whose loss of function contribute to leukemic transformation or tumor progression. Based on chromosome banding analysis, two critical regions have been identified, one in band q22 and another in bands q32-q35. Presently there are no data available on the molecular delineation of the distal critical region. In this study we analyzed bone marrow and blood samples from 13 patients with myeloid leukemia (de novo myelodysplastic syndrome [MDS] , n = 3; de novo acute myeloid leukemia [AML], n = 9; therapy-related (t-) AML, n = 1) which, on chromosome banding analysis, exhibited deletions (n = 12) or in one case a balanced translocation involving bands 7q31-qter using fluorescence in situ hybridization (FISH). As probes we used representative clones from a contig map of yeast artificial chromosome (YAC) clones that spans chromosome bands 7q31.1-qter. In the 12 cases with loss of 7q material, we identified a commonly deleted region of approximately 4 to 5 megabasepairs in size encompassing the distal part of 7q35 and the proximal part of 7q36. Furthermore, the breakpoint of the reciprocal translocation from the patient with t-AML was localized to a 1,300-kb sized YAC clone that maps to the proximal boundary of the commonly deleted region. Interestingly, in this case both homologs of chromosome 7 were affected: one was lost (−7) and the second exhibited the t(7q35). The identification and delineation of translocation and deletion breakpoints provides the first step toward the identification of the gene(s) involved in the pathogenesis of 7q35-q36 aberrations in myeloid disorders.